Technology and Entrepot Colonialism in Singapore, 1819-1940 - Goh, Chor Boon (Book collections on Project MUSE., 2013)
How did imported technology contribute to the development of the colony of Singapore? Who were the main agents of change in this process? Was there extensive transfer and diffusion of Western science and technology into the port-city? How did the people respond to change? Examining areas such as shipping, port development, telegraphs and wireless, urban water supply and sewage disposal, economic botany, electrification, food production and retailing, science and technical education, and health, this book documents the role of technology and, to a smaller extent, science, in the transformation.